El cuerpo : acontecimiento de lenguaje y discurso (2008)
ABSTRACT: Psychoanalysis allows to differentiate between organism and body, between those things that would be normal of animals and their instincts, in contrast with the man’s corporal construction, opposite to the corporal construction of men where it’s the pulsional and the force of the language what defines it’s condition. The corporality is then, a strict human phenomenon, but mainly, as it sample of the reading that Lacan does of Freud, the objective construction is an endeble construction in itself, and it could be manifested in symptoms that at the end show the complexity of the construction of the corporal things in the insertion in the symbolic.